Principal Strategy in Partnership Development - Sastramayani Sastramayani (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
This article aims to provide a conceptual overview of the principal's strategy in partnership development. The aspects studied are: 1) various dimensions of strategy; 2) The roles of school principals; and 3) Partnership development. The method used is a literature review, where the authors synthesize and develop various concepts and findings related to the principal's strategy in developing partnerships. The results of the study show that: first, strategy is a prerequisite in carrying out leadership roles. A reliable principal will be seen in his ability to read environmental conditions, internal and external, to formulate a grand design for school development. The concrete form is the formulation of the school's vision, mission, goals, and programs. Second, the roles of principals are increasingly complex in the midst of very fast environmental changes, as well as very tight competition between schools. Not only managerial roles, more than that the principal must appear as a leader who makes a difference. Third, partnership development is a deeper meaning of school quality. That schools do not exist in an empty space, but are directly connected to the community and the world of work as users of educational services. This article suggests the importance of increasing knowledge about strategy for school principals, followed up with technical skills in the strategy stages. Keywords: Strategy, School Management, Partnership, Quality